1995
DOI: 10.1073/pnas.92.23.10728
|View full text |Cite
|
Sign up to set email alerts
|

Glucose stimulation of insulin release in the absence of extracellular Ca2+ and in the absence of any increase in intracellular Ca2+ in rat pancreatic islets.

Abstract: Insulin secretion has been studied in isolated rat pancreatic islets under stringent Ca2l-depleted, Ca2+-free conditions. Under these conditions, the effect of 16.7 mM glucose to stimulate insulin release was abolished. Forskolin, which activates adenylyl cyclase, also failed to stimulate release in the presence of either low or high glucose concen- (6, 7). Another important effect of glucose with an enhancing effect on insulin release is time-dependent potentiation. This pathway too is Ca2+ dependent (14). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
1
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(108 citation statements)
references
References 23 publications
(18 reference statements)
7
97
1
3
Order By: Relevance
“…However, a Ca 2+ -independent pathway has also been proposed. Thus, Komatsu et al have suggested that both Ca 2+ -dependent and Ca 2+ -independent augmentation occurs via a pathway dependent on glucose metabolism [32,33]. In this context, we confirmed that adiponectin is able to stimulate insulin secretion when the influx of Ca 2+ through voltage-dependent Ca 2+ channels is blocked by nitrendipine; in other words, adiponectin stimulates insulin secretion without requiring influx of Ca 2+ through voltagedependent Ca 2+ channels.…”
Section: Discussionsupporting
confidence: 84%
“…However, a Ca 2+ -independent pathway has also been proposed. Thus, Komatsu et al have suggested that both Ca 2+ -dependent and Ca 2+ -independent augmentation occurs via a pathway dependent on glucose metabolism [32,33]. In this context, we confirmed that adiponectin is able to stimulate insulin secretion when the influx of Ca 2+ through voltage-dependent Ca 2+ channels is blocked by nitrendipine; in other words, adiponectin stimulates insulin secretion without requiring influx of Ca 2+ through voltagedependent Ca 2+ channels.…”
Section: Discussionsupporting
confidence: 84%
“…This K ATP channel-independent process is mostly considered as an amplification mechanism, which remains functionally silent unless [Ca 2+ ] i is elevated. Yet other studies have provided evidence that the K ATP channel-independent pathway may also exhibit triggering properties, since glucose under some conditions stimulates insulin release in a Ca 2+ -independent manner (Komatsu et al, 1995;Komatsu et al, 1996;Komatsu et al, 2001). The K ATP channel-independent pathway has remained elusive and many mechanisms have been proposed (reviewed in (Komatsu et al, 2001)).…”
Section: Role Of Metabolism For Glucose-induced Insulin Secretionmentioning
confidence: 99%
“…The basal glucose concentration used was 2.8 mmol/l, whereas the priming glucose concentration was 11.1 mmol/l in Ca 2ϩ -free conditions and 16.7 mmol/l in the presence of Ca 2ϩ . These are the optimal concentrations of glucose for the stimulation of insulin secretion in the absence and presence of Ca 2ϩ , respectively (22). Stimulation of islets in the test period, as distinct from the priming period, was always done with 16.7 mmol/l glucose in the presence of Ca 2ϩ .…”
Section: Methodsmentioning
confidence: 99%